Research trends in drama therapy: a bibliometric analysis based on Scopus - Korde, Žanete; Šuriņa, Sanita; Mārtinsone, Kristīne (Frontiers in Psychology, 2023)
Aim: As drama therapy has become increasingly important in healthcare, the number of scientific publications has increased, complicating the orientation in the research field. Therefore, the aim of this study is to provide a comprehensive overview of research trends in drama therapy, assessing the impact factors of publications and analyzing the research structure. Methods: 395 scientific articles indexed in Scopus were analyzed without time, geographic and language restrictions using bibliometric analysis methods - performance analysis, citation analysis, and science mapping. Data processing was performed using MS Excel, VOSviewer and Biblioshiny software. Results: The work of the pioneers of drama therapy continues to be actively cited, influencing the development of drama therapy. Today's leading researchers are increasingly engaging in collaborative research, working across disciplines and contributing to scientific progress. The hot topic of research is older adults and mental health. The diversity of terminology and the large volume of unpublished research point to the need for consolidation. Altmetric analysis would optimize the use of scientific information, promoting innovative research. Conclusions: This is the first study using the Scopus database to perform an extensive bibliometric analysis of research articles on drama therapy applying Biblioshiny and VOSviewer software. The results of the analysis reflect the evolution of the field from its historical roots to academic maturity, highlighting its current dynamic growth and the trend of drama therapy to establish itself as an interdisciplinary field in the healthcare system. This work serves as a valuable resource for the scientific community, professionals, students, and librarians in the field, helping to optimize the use of scientific resources in drama therapy and contributing to its future development.